PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU BUBUK MEREK L-MEN DI SEMARANG - Wisnu Pradityo Nugroho; Wahyu Hidayat; Hari Susanta Nugraha (Universitas Diponegoro, 2015)
This study aimed to determine the effect of product quality, price, and promotion of the product purchase decisions by first identifying, assessing and measuring consumer perceptions of the amount of sales of products in the market. Researchers conducted a study on the sale of milk powder products fitness L-Men in Semarang.This research was conducted with survey methods (interviews and questionnaires) to 100 (one hundred) of the respondents, the sampling selection technique using purposive sampling. The data obtained were analyzed quantitatively by using tools such as cross-table analysis, validity, reliability, simple linear regression, multiple linear regression, coefficient of determination and testing with T test curve and test curve F. The independent variable is the quality of the product, price and promotion, while the dependent variable is the purchase decision.The results showed no effect of product quality on purchasing decisions by 35.4%. The effect of price to quality is 35% of purchase decisions and influence on purchasing decisions promotion 40.6%. Taken together the quality of the product, price and promotion has the effect of 51.4%, which means that consumer perceptions of product, price and promotion proportional or positive, which if consumers assess the quality of the product, price, promotion of good will increase the sales of this product.Suggestions for the company is to continue to maintain the quality of products by regularly monitoring the quality of the basic ingredients of products, giving a discount on the purchase of products and continues to promote the increase of the personal selling product knowledge in order to provide solutions to customer needs appropriately is the key to success to improve consumer decision to buy powdered milk products of L-Men